Leader-Employee Interaction In The Virtual Workspace: The Effect Of Perceived Leadership Communication Quality Across Channels On Employees' Engagement Levels - Rautenbach, Casey (School of Management Studies, 2023)
Leader-member communications and employee engagement (EE) are critical for organisational success (Barhite, 2017; Kelly, 2021; Kohntopp & McCann, 2020). With a nearinstantaneous shift to remote work during the Covid-19 pandemic, the nature of communication between leaders and followers has changed (Alexander et al., 2020; Braier et al., 2021). In turn, there is uncertainty as to how leader-member communication exchanges and associated EE are facilitated among workers in the remote context (Abowd et al., 2020; Zeuge et al., 2020). Moreover, there is limited research on how to achieve appropriate leadership communication quality and EE enhancement in the virtual leadership-employee interactional context (Bark et al., 2015; Chanana, 2020). It is against this background that the proposed study sought to examine the extent to which leadership communication quality (LCQ), across different channels, affects the level of EE among South African remote employees. The present study assessed LCQ across the following channels: videoconferencing, telephone/audio-conferencing, e-mails, and companies' intranet instant messaging (IIM) channels. This study was founded in the theoretical integration of Social Exchange Theory (Homans, 1958) and Media Richness Theory (Daft & Lengel, 1984). The study hypothesised that greater perceived LCQ, through the use of richer channels, would increase EE among employees in the virtual workspace. A descriptive, cross-sectional, quantitative research design was conducted to examine the study's hypotheses. Data was gathered via an online self-report survey from South African (SA) employees that engaged in full-time and part-time remote working schedules (N = 179). Pearson correlation analyses confirmed positive relationships between the LCQ of each channel and EE. However, once all channels were combined in one multiple regression model, only the LCQ of video-conferencing channels was found to be a unique predictor of EE levels. Friedman tests revealed that the respondents' mean rankings of the two LCQ sub-facets assessed (communication clarity and leadership behaviour transmission) were higher for video-conferencing channels than for the other channels. Cumulatively, the research revealed that the channel associated with the highest LCQ was video-conferencing, and that leaders could most likely increase EE among their remote employees by using this channel compared to the other channels assessed. These results may contribute valuable insight to inform the development of digital leadership strategies and connectivity interventions in organisations for the future world of work.